Potassium-competitive acid blockers and advances in the management of patients with acid-related diseases: a narrative review - Qiao, Xinwei; Li, Peng (Frontiers in Physiology, 2025)
Traditional management of acid-related diseases, including gastroesophageal reflux disease, Helicobacter pylori infection, and peptic ulcer disease, primarily relies on proton pump inhibitors, which have notable limitations in acid suppression efficacy that hinder optimal treatment outcomes. Potassium-competitive acid blockers offer a novel approach with improved pharmacokinetic and pharmacodynamic properties, enhancing acid suppression and clinical efficacy in acid-related disease management. This narrative review evaluates the role of potassium-competitive acid blockers in acid-related disease management, comparing the pharmacokinetic, pharmacodynamic, clinical efficacy, and safety profiles of currently available agents. A comprehensive literature search from January 2002 to June 2024 was conducted across multiple databases to gather data on the efficacy and safety of potassium-competitive acid blockers. Potassium-competitive acid blockers showed comparable or superior clinical efficacy and generally comparable safety in various clinical settings vs. comparator proton pump inhibitors, particularly in managing erosive esophagitis, H. pylori eradication, and peptic ulcer disease. Potassium-competitive acid blockers, of which vonoprazan is the most well studied, offer comparable or improved therapeutic outcomes over traditional proton pump inhibitors, making them a valid option for several acid-related disease indications.